2020
DOI: 10.1123/jsr.2018-0165
|View full text |Cite
|
Sign up to set email alerts
|

Can the Use of Unstable Surfaces and Instruction for Conscious Abdominal Contraction Increase the EMG Activity of the Periscapular Muscles During the Dynamic Push-Up?

Abstract: Context: It is believed that conscious abdominal contraction (CAC) during exercise encourages greater periscapular activation through existing myofascial connections. On the other hand, it is postulated that the use of unstable surfaces would promote greater neuromuscular demand. Objective: To analyze the effect of CAC on periscapular muscle activity during push-up plus exercise on stable and unstable surfaces and to evaluate the correlation between electromyographic (EMG) activity of the serratus anterior (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Regarding external validity, eight studies included a representative sample of men and women ( Tucker et al, 2010 ; Maenhout et al, 2010 ; De Mey et al, 2014 ; Byrne et al, 2014 ; Herrington, Waterman & Smith, 2015 ; Youdas et al, 2018 ; Youdas et al, 2020a ; Biscarini, Contemori & Grolla, 2019 ) and only two reported dropouts throughout the study ( Byrne et al, 2014 ; Patselas et al, 2021 ). Regarding internal validity, ten of the included articles ( Martins et al, 2008 ; Tucker et al, 2010 ; De Araújo et al, 2011 ; De Araújo et al, 2018 ; De Araújo et al, 2020 ; Park et al, 2013 ; Kim et al, 2014 ; Pirauá et al, 2014 ; Karagiannakis, Athanasopoulos & Mandalidis, 2018 ; De Faria et al, 2021 ) carried out a physical evaluation of the participants to identify any clinical condition. In addition, only three studies ( Lee, Lee & Park, 2013 ; De Araújo et al, 2018 ; Biscarini, Contemori & Grolla, 2019 ) standardized movement velocity and phase duration of the exercises, and all of them included direct observation of participants during testing procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding external validity, eight studies included a representative sample of men and women ( Tucker et al, 2010 ; Maenhout et al, 2010 ; De Mey et al, 2014 ; Byrne et al, 2014 ; Herrington, Waterman & Smith, 2015 ; Youdas et al, 2018 ; Youdas et al, 2020a ; Biscarini, Contemori & Grolla, 2019 ) and only two reported dropouts throughout the study ( Byrne et al, 2014 ; Patselas et al, 2021 ). Regarding internal validity, ten of the included articles ( Martins et al, 2008 ; Tucker et al, 2010 ; De Araújo et al, 2011 ; De Araújo et al, 2018 ; De Araújo et al, 2020 ; Park et al, 2013 ; Kim et al, 2014 ; Pirauá et al, 2014 ; Karagiannakis, Athanasopoulos & Mandalidis, 2018 ; De Faria et al, 2021 ) carried out a physical evaluation of the participants to identify any clinical condition. In addition, only three studies ( Lee, Lee & Park, 2013 ; De Araújo et al, 2018 ; Biscarini, Contemori & Grolla, 2019 ) standardized movement velocity and phase duration of the exercises, and all of them included direct observation of participants during testing procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Only four articles ( Lehman, Gilas & Patel, 2008 ; Seo et al, 2013 ; De Mey et al, 2014 ; Herrington, Waterman & Smith, 2015 ) did not report the randomization of the exercises or support surface type. All the articles presented an appropriate normalization of the EMG signal, nevertheless only five studies ( Pirauá et al, 2014 ; Horsak et al, 2017 ; De Araújo et al, 2018 ; De Araújo et al, 2020 ; De Faria et al, 2021 ) randomized MVIC measurement, and one study ( Park et al, 2013 ) did not specify the statistical test performed for multifactorial analysis, only describing the pair comparison test. Lastly, four studies ( Martins et al, 2008 ; Gioftsos et al, 2016 ; Horsak et al, 2017 ; Patselas et al, 2021 ) included trial to trial reliability analysis among EMG measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Six PU variations met inclusion criteria and included: standard PU (n ¼ 17), 7,9,13,14,[18][19][20][21][22][23][24][25][26][27][28][29][30] PU plus (n ¼ 11), 11,12,18,20,29,[31][32][33][34][35][36] suspension system (n ¼ 7), 10,13,14,24,27,30,37 , hands on an unstable surface (n ¼ 6), 7,13,18,21,22,29 incline (n ¼ 3), 25,38,39 and incline with hands on an exercise ball (n ¼ 3). 25,38,39 Figures 1 and 3 provide representative images of these PU variations.…”
Section: Resultsmentioning
confidence: 99%
“…25,38,39 Figures 1 and 3 provide representative images of these PU variations. Five muscles met inclusion criteria, including: SA (n ¼ 17), 9,[11][12][13][18][19][20][21][22][23][24][28][29][30]34,35,38 UT (n ¼ 17), [10][11][12]14,18,19,[21][22][23]29,30,[32][33][34][36][37][38] pectoralis major (PM; n ¼ 13), 7,[10][11][12][24][25][26][27]30,31,34,37,39 middle and lower fibers ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation